SPS240 : Exercise methodology and physical conditioning for sport / Faculty of Sport Science and Recreation - UiTM, Faculty of Sport Science and Recreation (Universiti Teknologi MARA (UiTM), 2023)
This course emphasized the theoretical knowledge and practical application as they relate to physical conditioning. This course equips students with sound fundamental knowledge, understanding, skills and experience to design, implement and evaluate various training methods for the improvement of the fundamentals of fitness for the needs of sports performance.